Insurance Against Covariate Shocks : The Role of Index-Based Insurance in Social Protection in Low-Income Countries of Africa - Alderman, Harold (Washington, DC: World Bank, 2012)
Index insurance, such as weather indexing, addresses other inherent problems in insurance by using an indicator that is not affected by individual behavior and may address monitoring costs and moral hazard. A number of innovations using index insurance are being tried currently in diverse settings ranging from India to Mongolia to Malawi. Marketing costs may limit the provision of such insurance to small farmers, but even in such cases microfinance institutes may serve as market intermediaries. Moreover, state and submational governments can use insurance to achieve countercyclical funding programs. In this vein, municipal governments in Mexico have used insurance to finance disaster contingency while the World Food Program has insured a portion of its emergency assistance to Ethiopia. Humanitarian organizations and NGOs may also seek insurance in this manner.